Kinetic of Ascorbic Acid Dissolution in local pomegranate Juices - Doski, Rajab I.H. (Science Journal of University of Zakho, 2019)
This research was conducted to examine the impact of storage house time and storage house temperatures on ascorbic acid dissolution in pomegranate juice. The juice of pomegranate stored at the temperatures 15,25 and 35 C0for four months. Outcomes noted that in the case of rising temperature and period storage house let to reducing the ascorbic acid content.. The results of ascorbic acid dissolution kinetic parameter showed that the order of the reaction is first and there was an increasing in rate constant (K) in the case of increasing the storage house temperature. Also, the half time decreased with increasing the temperature of storage house. It was found that the shelf life of all samples decreased with increasing the storage house temperatures and storage house period.